2012
DOI: 10.1074/jbc.m111.322164
|View full text |Cite
|
Sign up to set email alerts
|

Arogenate Dehydratase Isoenzymes Profoundly and Differentially Modulate Carbon Flux into Lignins

Abstract: Background:The plastid-localized arogenate dehydratase (ADT) gene family is hypothesized to differentially control carbon flux for lignin deposition, with lignin being the main contributor to lignocellulosic recalcitrance. Results: Single and multiple ADT knock-outs resulted in differential control over lignin content/composition. Conclusion: The first evidence for Phe upstream metabolism differentially controlling carbon flux into distinct secondary cell wall types was discovered. Significance: Upstream metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 35 publications
3
49
0
Order By: Relevance
“…Interestingly, no T-DNA insertion knockout lines that abolish ADT2 mRNA are available (Corea et al , 2012 b ). This makes ADT2 unique and raises the possibility that an adt2 knockout is lethal.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, no T-DNA insertion knockout lines that abolish ADT2 mRNA are available (Corea et al , 2012 b ). This makes ADT2 unique and raises the possibility that an adt2 knockout is lethal.…”
Section: Discussionmentioning
confidence: 99%
“…7; Supplemental Table S6). Certain isoenzymes of arogenate dehydratase have been shown to profoundly and differentially modulate carbon flux into the downstream lignin biosynthesis pathway in Arabidopsis (Corea et al, 2012a(Corea et al, , 2012b. It seems likely that the induced genes in spruce encode isoenzymes responsible for the synthesis of Phe destined for monolignol and/or flavonoid biosynthesis, while some other isoenzymes are responsible for the formation of Phe utilized for protein synthesis.…”
Section: The Apoplastic Redox State Influences Cellular Metabolismmentioning
confidence: 99%
“…The eukaryotic host of the plant ancestor, or the free-living cyanobacterium that gave rise to the primary plastid, acquired both PPA-AT and ADT from an ancestor of Chlorobi/Bacteroidetes bacteria. The introduction of the PPA-AT and ADT enzymes allowed plants to synthesize Phe predominantly via the arogenate pathway (Jung et al, 1986;Maeda et al, 2010;Yoo et al, 2013), which currently supports the production of diverse and abundant phenylpropanoid natural products, including lignin (Corea et al, 2012b).…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical characterization of recombinant plant ADT enzymes showed that they have substrate preference toward arogenate over prephenate (Cho et al, 2007;Yamada et al, 2008;Maeda et al, 2010). Genetic analysis of plant ADTs further demonstrated that Phe is predominantly synthesized via the arogenate in plants (Maeda et al, 2010;Corea et al, 2012aCorea et al, , 2012b. However, phylogenetic analyses showed that the arogenate and prephenate specificity of ADH/PDH and ADT/PDT do not map tidily onto a single clade of the gene tree, suggesting that their substrate specificity has been gained and/or lost multiple times in the gene family's evolution (Jensen, 1985;Song et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation